Characterizing Microheterogeneity in Liquid Mixtures via Local Density Fluctuations - Lass, Michael; Kenter, Tobias; Plessl, Christian; Brehm, Martin (Entropy)
We present a novel approach to characterize and quantify microheterogeneity and microphase separation in computer simulations of complex liquid mixtures. Our post-processing method is based on local density fluctuations of the different constituents in sampling spheres of varying size. It can be easily applied to both molecular dynamics (MD) and Monte Carlo (MC) simulations, including periodic boundary conditions. Multidimensional correlation of the density distributions yields a clear picture of the domain formation due to the subtle balance of different interactions. We apply our approach to the example of force field molecular dynamics simulations of imidazolium-based ionic liquids with different side chain lengths at different temperatures, namely 1-ethyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride, which are known to form distinct liquid domains. We put the results into the context of existing microheterogeneity analyses and demonstrate the advantages and sensitivity of our novel method. Furthermore, we show how to estimate the configuration entropy from our analysis, and we investigate voids in the system. The analysis has been implemented into our program package TRAVIS and is thus available as free software.

'Topographisches‘ Schreiben: Lea Streisand. Paderborn Wintersemester 2022/23

‚Topographisches‘ Schreiben. Lea Streisand, Paderborn Wintersemester 2022/23: Die 41. Gastdozentur für Schriftstellerinnen und Schriftsteller. Zur Einführung. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Sich selbst erzählen. Lea Streisands autofiktionales Erzählen. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Lines in the Sand - Langer, Svenja

An Integrated Fuzzy Analytic Network Process and Fuzzy Regression Method for Bitcoin Price Prediction - Amiri, Arman; Tavana, Madjid; Arman, Hosein (Internet of Things)
Keywords: Management of Technology and Innovation; Artificial Intelligence; Computer Science Applications; Hardware and Architecture; Engineering (miscellaneous); Information Systems; Computer Science (miscellaneous); Software

Data-driven simulation-based decision support system for resource allocation in industry 4.0 and smart manufacturing - Mahmoodi, Ehsan; Fathi, Masood; Tavana, Madjid; Ghobakhloo, Morteza; Ng, Amos H.C. (Journal of Manufacturing Systems)
Keywords: Industrial and Manufacturing Engineering; Hardware and Architecture; Software; Control and Systems Engineering

A systematic review of the soft computing methods shaping the future of the metaverse - Tavana, Madjid; Sorooshian, Shahryar (Applied Soft Computing)
Keywords: Software

Einführung - Wortmann, Fabio; Kämmerling, Sina; Hemmrich, Simon; Gradert, Till; Ellermann, Kai (Digitale Plattformen im industriellen Mittelstand. Strategien, Methoden, Umsetzungsbeispiele)

Digitale Plattformen im industriellen Mittelstand

Digitale Plattformen im industriellen Mittelstand

Grundlagen - Hemmrich, Simon; Wortmann, Fabio; Lüttenberg, Hedda; Gradert, Till; Kämmerling, Sina; Meyer, Maurice (Digitale Plattformen im industriellen Mittelstand. Strategien, Methoden, Umsetzungsbeispiele)

Digitale Plattformen - Strategien und Methoden - Kämmerling, Sina; Gradert, Till; Wortmann, Fabio; Hemmrich, Simon; Lüttenberg, Hedda; Meyer, Maurice (Digitale Plattformen im industriellen Mittelstand. Strategien, Methoden, Umsetzungsbeispiele)

Evaluation of the Influence of Particle Type, Shape and Size on the Thermal Conductivity of Filled Polymers in the Fused Filament Fabrication Process - Moritzer, Elmar; Elsner, Christian Lennart
The Fused Filament Fabrication (FFF) process is increasingly used for the manufacturing of individualized and complex structures, which continuously results in new requirements regarding the material properties. A characteristic material property for polymers is the low thermal conductivity. However, for specific applications, such as additively manufactured injection molding tool inserts, increased thermal conductivity is advantageous. In this study, the influence of fillers of different types, shapes and sizes on the resulting thermal conductivity of compounds is investigated. The aim is to analyze the effects of the fillers, considering the FFF-typical strand structure. The first step is to characterize the fillers in terms of shape and size. Based on this, the resulting thermal conductivity of specimens manufactured in the FFF process for different build orientations is specifically examined and compared to injection molding. This ensures that the process- and material-related anisotropy of the specimens is considered in the analysis. For the evaluation, a methodology is developed to be applied in Laser Flash Analysis (LFA), which allows the results to be evaluated despite the characteristic FFF surface structure. For the final visualization of the influence of the particle size on the particle orientation, Scanning Electron Microscopy (SEM) images of the relevant polymer compounds are made. The investigations provide a data basis regarding the influence of the particle type, shape and size on the thermal conductivity as well as for the requirement-oriented selection of fillers for processing thermally conductive polymer compounds in the FFF process.

„Vom Schieben und geschoben werden…“ Grundlegungen zu einer multiperspektivischen Qualifizierung (mpQ) zur Förderung multiprofessioneller Teamarbeit (mpT) im Kontext inklusiver Bildung - Kückmann, Marie-Ann (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Wiederholt wird im Kontext inklusiver Bildung auf die Relevanz multiprofessioneller Teamarbeit verwiesen und darauf aufbauend werden auch zunehmend angemessene Qualifizierungskonzepte für pädagogische Fachkräfte eingefordert. Bei der Sichtung bestehender Angebote fällt dann aber auf, dass diese den Blick häufig primär auf Erfolgsfaktoren für die Teamentwicklung und damit die vorzufindenden kollektiven Strukturen richten, wodurch die Gefahr besteht, dass die individuellen, berufsbiografischen Perspektiven im Prozess entsprechend wenig beleuchtet werden oder aber ganz unberücksichtigt bleiben. Auch Einblicke in den Forschungsstand veranschaulichen die verbundene Komplexität und heben dabei teils auch bereits individuelle, interaktionelle, institutionelle und gesellschaftliche Perspektiven hervor. Dabei wird jedoch nicht immer klar expliziert, welche individuellen, kollektiven oder verbindenden Verständnisse sozialen Handelns der Forschungsarbeit jeweils zugrunde liegen. Diesbezüglich fehlen u. U. Referenzsysteme, die die Komplexität des sozialen Konstrukts multiprofessioneller Teamarbeit im Spannungsfeld von sowohl Struktur- als auch Handlungsmomenten aufnehmen und entsprechenden Qualifizierungskonzepten überhaupt zugrunde gelegt werden können. Der vorliegende Artikel widmet sich diesem Anspruch, versucht diesbezüglich sowohl aus theoretischer als auch aus empirischer Perspektive vertiefende Einsichten in die multiprofessionelle Teamarbeit im Kontext inklusiver Bildung zu eröffnen, hierauf aufbauend erste Anschlussstellen für mögliche Qualifizierungskonzepte auszuweisen und soll so einen Ausgangspunkt für eine wissenschaftlich fundierte Gestaltungsarbeit anbieten. Abstract The relevance of multi-professional teamwork is often mentioned in the context of inclusive education. The need for qualification concepts for teaching staff is also increasing. However, existing qualifications often focus primarily on collective structures. This involves the risk of reducing the content and not taking individual, professional biographical perspectives into account sufficiently. Insights into current research illustrate the associated complexity and, in some cases, also emphasise individual, interactional, institutional and social perspectives. However, it is not always clear which individual and/or collective understandings of social action underpin the research. In this sense, there is a lack of reference systems that address the complexity of the social construct of multi-professional teamwork integrating both structural as well as individual perspectives. The aim of this paper is to analyse what constitutes multi-professional teamwork and how it is related to the individual development of its members. Based on an extensive examination of its theoretical as well as empirical underpinnings, it lays the foundation for an ongoing productive discussion about suitable qualification concepts in this context.

Research on curriculum resources in mathematics education: a survey of the field - Rezat, Sebastian (ZDM – Mathematics Education)

Digitalisierung als Chance für alle Prinzipien guten Unterrichts - Barzel, Bärbel; Greefrath, Gilbert; Nagel, Mareike; Hoffmann, Max (mathematik lehren)
athematische Kompetenzen digital zu fördern und digitale Kompetenzen mathematisch zu fördern – dies ist eine Forderung der neuen Bildungsstandards mit Blick auf eine Bildung in der digitalen Welt. Gerade das Potenzial digitaler Medien für das fachliche Lernen wurde in vielen Studien bestätigt. Eine sinnvoll gestaltete Einbettung digitaler Medien bietet die Chance, allen fünf Prinzipien eines guten Unterrichts gerecht zu werden: Verstehensorientierung, Durchgängigkeit, kognitive Aktivierung, Lernendenorientierung & Adaptivität und Kommunikationsförderung. Die flächendeckende Nutzung digitaler Medien etabliert sich bislang nur zögerlich. Aber wie können wir Lehrkräfte stärken, digitale Medien sinnvoll einzusetzen? Wir möchten hier die Bandbreite der Möglichkeiten an Beispielen verdeutlichen, ihren Einsatz motivieren und Wege für einen guten Unterricht aufzeigen.

31 Sprachbildung im berufsbezogenen Mathematikunterricht. - Prediger, Susanne; Wessel, Lena (Berufs-und Fachsprache Deutsch in Wissenschaft und Praxis)

What Price Culture? – A Taxonomy of the Admission Pricing Policy at Museums - Althaus, Maike; Müller, Stefanie Jutta Marianne; Kundisch, Dennis (International Journal of Cultural Policy)
An admission pricing policy should allow a museum to facilitate access to cultural education and heritage while contributing to its economical sustainability. Despite the importance of this matter to museums, design-relevant knowledge on the configuration of the admission pricing policy in museums remains limited, resulting in museum decision-makers lack the necessary understanding of how to customize their admission pricing policy, and researchers the foundation for advancing knowledge on the topic. To address these issues, we draw on a well-established development method to build a taxonomy, which involved synthesising the literature on the admission pricing policy of museums, analysing the characteristics of the admission pricing policy of 149 museums, and creating a cluster analysis for 117 museums located in the same region. The analysis yielded three distinct clusters (namely, free admission pricing policy, simple admission pricing policy, comprehensive admission pricing policy). Our work supports practitioners by showing them different options for structuring an admission pricing policy, while providing researchers with a foundation for further investigating museums’ admission pricing policies.

Hierarchical Taxonomies in Information Systems - Nickerson, Robert C.; Varshney, Upkar; Muntermann, Jan; Kundisch, Dennis (Proceedings of Thirtieth Americas Conference on Information Systems (AMCIS))